Pemetaan Alat Permainan Edukatif Indoor dan Outdoor dalam Menunjang Aspek Perkembangan Fisik Motorik di Taman Kanak-kanak Kecamatan Praya Kabupaten Lombok Tengah - Baik Nilawati Astini; Nurhasanah Nurhasanah; I Nyoman Suarta; Baiq Nunike Sulvia Dewi (Indonesian Publication Center, 2022)
The purpose of this study was to find out what indoor and outdoor educational game tools develop physical motor skills in Kindergarten, Praya subdistrict and to find out what indoor and outdoor educational game tools are dominantly used in developing children's motor skills in kindergarten, Praya subdistrict, Central Lombok regency. This type of research is survey research with descriptive quantitative method approach. In this study using a questionnaire method in the form of standard written questions, collecting data in this study using a checklist, questionnaires were distributed to 10 kindergartens in Praya sub-district, Central Lombok regency. The data analysis used in this research is the percentage using a quantitative descriptive approach. Based on the results of research that has been done, the number of Indoor and Outdoor APE used in developing children's motor skills in Praya District, Central Lombok Regency, Kindergartens that have Indoor APE are 70.1% and Kindergartens who have Outdoor APE are 45.3%. and which are often used from several types of Indoor APE as much as 36.9%. Then those that are often used from several types of Outdoor APE are as much as 43%. Based on the percentage results that have been obtained, it can be concluded that of the ten Kindergartens in Praya sub-district more have Indoor APE with the highest percentage of 70.1% than Outdoor APE, but APE is more dominantly used by children, namely Outdoor APE with a percentage of 43%.